O efeito da psicoeducação baseada em atenção plena no vício em internet em adolescentes. - Esmaeilzadeh, Samineh; Elyeli, Kemal; Necipoğlu, Dilay (Acta Paulista de Enfermagem, 2025)
The article investigates the levels of internet addiction among adolescent nursing students at a university in Northern Cyprus and evaluates the impact of a mindfulness-based psychoeducation program on these students. The study, conducted between December 2023 and March 2024, included a descriptive phase and a quasi-experimental phase with pre-test and post-test, involving 26 students with high levels of internet addiction. The results showed a significant reduction in internet addiction levels and an increase in present-moment awareness after the intervention, indicating the effectiveness of the mindfulness program. The study suggests the need for prevention programs and training on healthy internet use for adolescents.